2011
DOI: 10.3109/01902148.2011.641139
|View full text |Cite
|
Sign up to set email alerts
|

Resilience of the human fetal lung following stillbirth: Potential relevance for pulmonary regenerative medicine

Abstract: Recent advances in pulmonary regenerative medicine have increased the demand for alveolar epithelial progenitor cells. Fetal lung tissues from spontaneous pregnancy losses may represent a neglected, yet ethically and societally acceptable source of alveolar epithelial cells. The aim of this study was to determine the regenerative capacity of fetal lungs obtained from second trimester stillbirths. Lung tissues were harvested from 11 stillborn fetuses (13–22 weeks’ gestation) at post-delivery intervals ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Samples for transplantation (1–2 mm 3 pieces) were taken from the peripheral parenchyma of the right lung. Transplantation was performed at the Xenotransplant Core Facility at Brown University (Providence, RI), as previously described 20, 21 . Recipients of the renal subcapsular xenografts were 6 to 12-week-old male SCID-beige mice (Fox Chase SCID beige, Charles River, Wilmington, MA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples for transplantation (1–2 mm 3 pieces) were taken from the peripheral parenchyma of the right lung. Transplantation was performed at the Xenotransplant Core Facility at Brown University (Providence, RI), as previously described 20, 21 . Recipients of the renal subcapsular xenografts were 6 to 12-week-old male SCID-beige mice (Fox Chase SCID beige, Charles River, Wilmington, MA).…”
Section: Methodsmentioning
confidence: 99%
“…In the course of recent studies that employed a human-to-rodent fetal lung xenograft model 20, 21 , we identified unusual patterns of microvascular growth in a subset of human fetal lung grafts. The microscopic appearance of these aberrant vascular patterns was strongly reminiscent of the microvascular dysmorphism previously described in postmortem studies of premature ventilated infants and infants with BPD 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This period was chosen for tissue acquisition because it is an important period of organogenesis in human fetal prostate 12 . De Paepe et al provides a detailed description of tissue procurement 22 . Briefly, written and informed consent is obtained from donors, and a board certified pathologist evaluated the condition of the human tissue prior to implantation.…”
Section: Methodsmentioning
confidence: 99%
“…This model has shown promise for toxicologic studies. In general, we have found that human fetal lung xenotransplants are viable and exhibit brisk proliferative and secretory activity (De Paepe et al., , ). However, lung grafts have a mildly dysplastic appearance, reminiscent of the previously described features of fetal lungs following in utero tracheal occlusion (De Paepe et al., ).…”
Section: Human Fetal Lung Xenotransplantation To Study Tissue Remodelingmentioning
confidence: 98%
“…In this review, we describe our recent development of xenotransplant models with the goal of studying the effects of xenobiotics in human fetal testis (Heger et al., ; Spade et al., ), prostate (Saffarini et al., ), lung (De Paepe et al., , ), liver, and adipose tissue (Garcia et al., ). We do not aim to conduct an exhaustive review of the extensive literature on xenotransplantation.…”
Section: Introductionmentioning
confidence: 99%